THE ORIGIN OF CHALICOTHERES (PERISSODACTYLA, MAMMALIA) - Hooker J.J.; Dashzeveg D. (My University, 2004)
Description of a new genus of perissodactyl, Protomoropus, for the species ‘Hyracotherium’gabuniai Dashzeveg and its inclusion with a diversity of other primitive perissodactyls in a cladistic analysis results in the following higher order changes to our knowledge of perissodactyl phylogeny. Protomoropus is sister taxon to the Chalicotheriidae plus Lophiodontidae, which themselves are confirmed as sister groups. The previously monofamilial superfamily Chalicotherioidea is extended to include all three taxa. Paleomoropus and Lophiaspis are shown to be primitive lophiodontids. Various genera of the Isectolophidae are shown to be stem members of a clade that includes chalicotheres and lophiodonts. The infraorder Ancylopoda is extended to include them. Inclusion of isectolophids in the Ancylopoda rather than as stem tapiromorphs results in the break up of the clade Tapiromorpha. Instead, the modern perissodactyl groups, comprising the horse superfamily Equoidea and that of the rhinos and tapirs, the Ceratomorpha (here reduced in rank to parvorder), form a new clade which is here named infraorder Euperissodactyla nov. The Brontotheriidae form the sister group to Ancylopoda plus Euperissodactyla. The clade comprising Ancylopoda plus Euperissodactyla is named suborder Lophodontomorpha nov. The Chalicotherioidea and Chalicotheriidae evolved in Asia. The Lophiodontidae arose following dispersal from Asia to North America. Dispersal continued to Europe, where the family radiated.
Keywords: Mongolia; cladistics; systematics; Lophiodontidae; Ancylopoda; palaeobiogeography